Discussion of “Anomalous stock returns around internet firms’ earnings announcements” - Berger, Philip G. (Journal of Accounting and Economics, 2003)
Trueman, Wong, and Zhang (TWZ) investigate an apparent anomaly in the pricing of internet firms around their earnings announcements, which they attribute to price pressure. The discussion addresses three concerns. The paper is unusual in choosing an event (earnings announcements) that does not appear to have an obvious non-information-related reason for triggering unjustified changes in demand for the firm's shares. Relatedly, there are limitations to the tests made of the price pressure hypothesis. Finally, the discussion elaborates on TWZ's brief mention of the difficulties with implementing a profitable trading strategy based on the stock return pattern they document.